Problemy przekładu specjalistycznego na przykładzie tekstów z dziedziny prawa, biologii, biotechnologii i medycyny - Kłos, Patrycja; Matulewska, Aleksandra; Nowak-Korcz, Paulina (Investigationes Linguisticae, 2007)
This article deals with the analysis of problems in translation of EU directives from English into Polish. The examples were taken from three directives regulating medicine, biology and biotechnology-related matters. The authors have discussed the translation problems and classified mistakes and errors identified in the Polish-language versions and have given their translation suggestions. A short description of characteristic features of selected problems has been given. The authors also discuss the main roots of problems occurring in translations of texts formulated in more than one LSP.